Comparison Between Isotropic 3-Dimensional Fat-Suppressed T2-Weighted Fast Spin Echo (FSE) and Conventional 2-Dimensional Fat-Suppressed Proton-Weighted FSE Shoulder Magnetic Resonance Imaging at 3-T in Patients With Shoulder Pain. Issue 4 (July 2018) - Horiuchi, Saya; Nozaki, Taiki; Tasaki, Atsushi; Ohde, Sachiko; Deshpande, Gautam A.; Starkey, Jay; Hara, Takeshi; Kitamura, Nobuto; Yoshioka, Hiroshi
Abstract : Objective: The aims of this study were to compare isotropic 3-dimensional fat-suppressed T2-weighted fast spin echo (FSE) imaging (T2FS) with 2-dimensional fat-suppressed proton-density–weighted FSE imaging (2D-PDFS) and evaluate feasibility of isotropic 3-dimensional FSE shoulder imaging at 3-T magnetic resonance imaging (MRI). Methods: Seventy-eight patients who underwent shoulder MRI were evaluated. Three-dimensional T2FS and 2D-PDFS were qualitatively graded for delineation of anatomic structures. In quantitative analysis, mean relative signal intensity and relative signal contrast between each structure of the shoulder were compared. Results: Three-dimensional T2FS showed significantly higher scores for rotator cuff ( P = 0.020), lower scores for bone ( P < 0.001), and higher relative contrast of rotator cuff to fluid ( P < 0.001) and labrum to fluid ( P < 0.001) in comparison with 2D-PDFS. No significant difference in relative signal intensity of the rotator cuff, labrum, joint fluid, cartilage, and bone marrow was demonstrated. Conclusions: Isotropic 3-dimensional FSE MRI has similar image quality and diagnostic performance to conventional 2-dimensional sequence in evaluation of the rotator cuff.